2022
DOI: 10.23887/jstundiksha.v11i2.45983
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTERISASI KIMIA DAN SENSORI COOKIES NON-GLUTEN DENGAN SUBTITUSI TEPUNG TULANG IKAN TONGKOL (Euthynnus affinis) SEBAGAI ALTERNATIF MAKANAN RINGAN PENDERITA CELIAC

Abstract: Celiac adalah penyakit genetik dengan prevalensi kasus rendah yang menyebabkan penderitanya mengalami gangguan usus halus apabila mengonsumsi pangan mengandung gluten. Penderita Celiac biasanya membatasi konsumsi gluten dalam makanan ringan dari sumber lainnya. Singkong merupakan salah satu komoditas pertanian lokal unggulan Indonesia yang dapat dimanfaatkan sebagai bahan baku pangan non-gluten. Tujuan penelitian ini adalah mengevaluasi komposisi kimia dan tingkat kesukaan panelis terhadap cookies non-gluten d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The ash content of tuna bone flour showed a high value of 57.251%. Some researchers also reported that fish bone flour tends to be high, namely tilapia bone flour of 75.83% [16]; tuna bone flour of 84.22% [3]; belida fish bone flour of 88.13% [17]; catfish bone flour of 59.49% [18]; cob fish flour of 60.97% [19]. Tababaka [20] reported that the high ash content of fish bones is caused by the main constituent component of fish bones, namely minerals.…”
Section: Ash Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…The ash content of tuna bone flour showed a high value of 57.251%. Some researchers also reported that fish bone flour tends to be high, namely tilapia bone flour of 75.83% [16]; tuna bone flour of 84.22% [3]; belida fish bone flour of 88.13% [17]; catfish bone flour of 59.49% [18]; cob fish flour of 60.97% [19]. Tababaka [20] reported that the high ash content of fish bones is caused by the main constituent component of fish bones, namely minerals.…”
Section: Ash Contentmentioning
confidence: 99%
“…This is thought to be due to the roasting process and the addition of raw materials in the form of fish bone flour into cookies. Andayani [19] stated that the color intensity of cookies can be influenced by several factors such as baking time, weight and size of cookies, and raw materials used.…”
Section: Colormentioning
confidence: 99%
See 1 more Smart Citation